Crisis of higher education in Russia - Vakhitov R.R.; Rodionova A.E.; Smirnova E.V.; Mukhutdinov R.H.; Arzhakova M.I.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
The article is devoted to the analysis of the causes of the higher education crisis in Russia in the post-Soviet period. The authors proceed from the point of view that the basis of modern civilization is industry and therefore the fundamental function of higher education is to train specialists for industry and the socio-economic sphere of society. Thus, there is a steady correlation between the type of economy and the type of higher education. The universities of the West (the Humboldt model) with their academic freedoms are ideally suited to a market-type economy, Soviet universities with their authoritarianism in the learning process-to the Soviet, socialist, planned economy.The problems of the post-Soviet higher education are related to the fact that universities, adapted to the planned economy, are now forced to function in a society that has shifted to a certain extent to the market model. BEIESP.